2021
DOI: 10.53378/348729
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Factors and its Influence on the Job Performance of Non-academic Staff in a University

Abstract: The human capital is unarguably an important element that completes any organization. With proper motivation, these people work towards quality products and services. Question arises on non-teaching personnel of academic institutions as support staff. This study focuses on the work motivations and job performance of non-teaching personnel in a university. This descriptive research used structured questionnaire for the self-assessment of the 50 administrative and support staff. The results of the study proved t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…It is recognized as a big challenge and an efficient component of work success, and a must to direct workers to vital targets (Ghaffari et al, 2017). Several studies have shown empirically that motivational factors are very positive in improving employee performance (Ghaffari et al, 2020;Manalo & Apat, 2021;Niati et al, 2021). Kodwani & Prashar (2019) in their research found that motivation aided by training may increase job performance.…”
Section: Relationship Between Motivation and Job Performancementioning
confidence: 99%
“…It is recognized as a big challenge and an efficient component of work success, and a must to direct workers to vital targets (Ghaffari et al, 2017). Several studies have shown empirically that motivational factors are very positive in improving employee performance (Ghaffari et al, 2020;Manalo & Apat, 2021;Niati et al, 2021). Kodwani & Prashar (2019) in their research found that motivation aided by training may increase job performance.…”
Section: Relationship Between Motivation and Job Performancementioning
confidence: 99%
“…Employee motivation is simply the rationale behind employees' actions and behaviours, as impacted by the traits, circumstances, or passion that push them to pursue and fulfil professional goals and obligations (Zumrah, 2022). Motivation can be described as a psychological force guiding an individual's conduct within an organization, influencing both their degree of effort www.scholink.org/ojs/index.php/jbtp and persistence in challenging circumstances (Manalo et al, 2021). Motivational factors are human psychological features that influence a person's level of commitment to a goal.…”
Section: Concept Of Motivationmentioning
confidence: 99%
“…Intrinsically motivated non-academic staff influences the quality-of-service delivery, innovation, commitment, collaboration, adaptability, and overall organizational climate. Fostering intrinsic motivation among nonacademic staff through supportive leadership, recognition of achievements, opportunities for professional development, and a positive work environment can yield significant benefits for the university as a whole (Manalo, & Apat, 2021). In spite of these, the performance of non-academic staff at the University of Eldoret (UoE) has been interrupted due to industrial disputes involving both the employer and employees.…”
Section: Statement Of the Problemmentioning
confidence: 99%